2015
DOI: 10.1039/c4bm00397g
|View full text |Cite
|
Sign up to set email alerts
|

Mineralized collagen scaffolds induce hMSC osteogenesis and matrix remodeling

Abstract: Biomaterials for bone tissue engineering must be able to instruct cell behavior in the presence of the complex biophysical and biomolecular environments encountered in vivo. While soluble supplementation strategies have been identified to enhance osteogenesis, they are subject to significant diffusive loss in vivo or the need for frequent re-addition in vitro. This investigation therefore explored whether biophysical and biochemical properties of a mineralized collagen-GAG scaffold were sufficient to enhance h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 73 publications
(133 reference statements)
8
108
0
Order By: Relevance
“…We have previously reported that the MC-GAG scaffold is a highly osteogenic material for primary bone marrow-derived mesenchymal stem cells characterized with a porosity of 85 ± 3 % [24] , pore size of 156 ± 6 μm [19, 24] , and morphology of isotropic pores with a transverse:longitudinal pore aspect ratio of 0.95 ± 0.01 [19] . In comparison to non-mineralized collagen glycosaminoglycan scaffolds, MC-GAG has an increased stiffness and the ability to release calcium and phosphate ions from the scaffold into culture, which may be contributors to the osteogenic capabilities [17, 25] . Although we have shown that MC-GAG induces osteogenesis efficiently in the absence of BMP-2 [15, 22] , BMP-9 has been demonstrated to be the most osteogenic BMP family member in both in vitro and in vivo ectopic mineralization studies using C3H10T1/2 cells and C2C12 cells [3, 26] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the MC-GAG scaffold is a highly osteogenic material for primary bone marrow-derived mesenchymal stem cells characterized with a porosity of 85 ± 3 % [24] , pore size of 156 ± 6 μm [19, 24] , and morphology of isotropic pores with a transverse:longitudinal pore aspect ratio of 0.95 ± 0.01 [19] . In comparison to non-mineralized collagen glycosaminoglycan scaffolds, MC-GAG has an increased stiffness and the ability to release calcium and phosphate ions from the scaffold into culture, which may be contributors to the osteogenic capabilities [17, 25] . Although we have shown that MC-GAG induces osteogenesis efficiently in the absence of BMP-2 [15, 22] , BMP-9 has been demonstrated to be the most osteogenic BMP family member in both in vitro and in vivo ectopic mineralization studies using C3H10T1/2 cells and C2C12 cells [3, 26] .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging efforts have begun to shift focus from homogenous biomaterials for the purpose of regenerating a single tissue (Caliari et al, 2011; Ferreira et al, 2012; Galatz et al, 2006; Kanungo et al, 2008; Levingstone et al, 2014; Mathew et al, 2012) to multi-compartment and spatially graded biomaterials for the express purpose of repairing more complex tissues such as the tendon-to-bone junction (Caliari et al, 2015a; Harley et al, 2010; Lipner et al, 2014; Qu et al, 2013; Smith et al, 2016; Weisgerber et al, 2015; Weisgerber et al, 2013b). Efforts in our lab have recently described two new variants of collagen scaffolds under development for osteotendinous repair applications.…”
Section: : Introductionmentioning
confidence: 99%
“…The combination of collagen and mineral content has been evaluated previously and found to have promise in osteoconduction and bone healing, although the mechanism remains unknown and the superiority of such scaffolds in comparison to other types of scaffolds are unclear [2023]. We have found that combining both the organic and inorganic components of the ECM in the form of a novel nanoparticulate mineralized collagen glycosaminoglycan (MC-GAG) scaffold results in a highly osteogenic and structurally stable scaffold for both primary rabbit bone marrow stromal cells and primary human mesenchymal stem cells [18,19,24,25]. In this work, we investigate osteogenic differentiation of human mesenchymal stem cells on MC-GAG scaffolds in conjunction with BMP-2 stimulation.…”
Section: Introductionmentioning
confidence: 99%